La personalidad lingüística y el análisis del texto. Reflexiones en torno de una experiencia docente - Drosdov Díez, Tatiana (Eslavística Complutense, 2003)
The aim of the present article is to illustrate the role, which language consciousness and language personality play in the discourse analysis and translation.
Keywords: Discourse análisis; Translation; Language personality; Language conciousness